The Influence of Human Resources Level, Internal Control, Information Technology on The Quality of Financial Reports (Study Case UD Central Buana Motor) - Angelica Stefanny Ahliawan; Suwignyo Widagdo; Wiwik Fitria Ningsih (Future Science, 2022)
The phenomenon of very tight competition in business requires companies to be able to apply the right strategy in accordance with the market conditions they face and have quality reports so that research is conducted which aims to analyze the Effect of Competency Levels of Human Resources, Internal Control Systems, Utilization of Information Technology on the Quality of Financial Reports At UD Central Buana Motor Bondowoso. This type of research used is quantitative research. The data used are primary data and secondary data with data collection techniques namely observation, interviews, document recording, questionnaires/questions. Data collection techniques using a questionnaire a number of 30 respondents or people. The sampling technique used a saturated sample, namely all populations were sampled in this study, namely all employees of UD Central Buana Motor Bondowoso. The population in this study is UD Central Buana Motor. The data analysis method used is the data instrument test, classical assumption test, multiple regression analysis, hypothesis testing and the coefficient of determination. Testing data using the SPSS application version 22. After conducting research at UD Central Buana Motor Bondowoso, the results obtained showed that the level of competence of human resources, internal control systems, and utilization of information technology had a partial effect on the quality of financial reports. Simultaneously the level of competence of human resources, internal control systems, use of information technology affect the quality of financial reports.